Alternative Ni-Impregnated Mixed Ionic-Electronic Conducting Anode for SOFC Operation at High Fuel Utilization. Issue 10 (1st January 2017) - Futamura, S.; Tachikawa, Y.; Matsuda, J.; Lyth, S. M.; Shiratori, Y.; Taniguchi, S.; Sasaki, K.
Abstract : Redox-stable anodes are developed for zirconia-based electrolyte-supported SOFCs in order to improve the durability against fuel supply interruption and for higher fuel utilization, as an alternative to the conventional Ni-YSZ cermet. GDC (Ce0.9 Gd0.1 O2 ) is utilized as a mixed ionic-electronic conductor (MIEC), and combined with LST (Sr0.9 La0.1 TiO3 ) as an electronic conductor. Ni catalyst nanoparticles are incorporated via impregnation. The electrochemical characteristics of SOFC single cells using these anode materials are investigated in humidified H2 at 800°C. The stability against redox cycling and under high fuel utilization is analyzed and discussed. Ni-impregnated anodes with dispersed Ni catalyst nanoparticles on conducting oxide LST-GDC backbones exhibit lower anode non-ohmic overvoltage, and improve I-V performance. These anodes also show better redox stability compared to conventional anodes because of the isolation of Ni catalysts, preventing their agglomeration. Moreover, the co-impregnation of Ni catalysts and GDC nanoparticles further improves electrochemical characteristics due to a decrease in anode ohmic (IR) loss and non-ohmic overvoltage. This anode shows comparable I-V performance to conventional anodes for typical humidified hydrogen fuels, and is a promising redox-stable alternative for application at high fuel utilization.